Autophagy and inflammation an intricate affair in the management of obesity and metabolic disorders: evidence for novel pharmacological strategies? - Friuli, Marzia; Sepe, Christian; Panza, Elisabetta; Travelli, Cristina; Paterniti, Irene; Romano, Adele (Frontiers in Pharmacology, 2024)
Unhealthy lifestyle habits including a sedentary life, the lack of physical activity, and wrong dietary habits are the major ones responsible for the constant increase of obesity and metabolic disorders prevalence worldwide; therefore, the scientific community pays significant attention to the pharmacotherapy of such diseases, beyond lifestyle interventions, the use of medical devices, and surgical approaches. The intricate interplay between autophagy and inflammation appears crucial to orchestrate fundamental aspects of cellular and organismal responses to challenging stimuli, including metabolic insults; hence, when these two processes are dysregulated (enhanced or suppressed) they produce pathologic effects. The present review summarizes the existing literature reporting the intricate affair between autophagy and inflammation in the context of metabolic disorders, including obesity, diabetes, and liver metabolic diseases (non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH)). The evidence collected so far suggests that an alteration of autophagy might lead to maladaptive metabolic and inflammatory responses thus exacerbating the severity of the disease, and the most prominent conclusion underlies that autophagy might exert a protective function by contributing to balance inflammation. However, the complex nature of obesity and metabolic disorders might represent a limit of the studies; indeed, although many pharmacological treatments, producing positive metabolic effects, are also able to modulate autophagic flux and inflammation, it is not clear if the final beneficial effect might occur only by their mechanism of action, rather than because of additionally involved pathways. Finally, although future studies are needed, the observation that anti-obesity and antidiabetic drugs already on the market, including incretin mimetic agents, facilitate autophagy by dampening inflammation, strongly contributes to the idea that autophagy might represent a druggable system for the development of novel pharmacological tools that might represent an attractive strategy for the treatment of obesity and metabolic disorders.